Advanced integration of stereotaxis and real-time MRI for precise and safe medical navigation: a future paradigm for minimally invasive interventions - Lorenzo Söderholm Raygo; Wojcieszynski Puder Tonutti (Vertex, 2023)
Minimally invasive techniques have transformed medicine by improving patient outcomes and reducing invasiveness. Existing navigation methods, which use fluoroscopy or pre-operative imaging, lack real-time visualization and precision during complex surgeries. Fluoroscopy may also expose patients and medical staff to ionizing radiation. We propose enhanced stereotaxis and real-time magnetic resonance imaging (MRI) integration to overcome these problems and improve minimally invasive intervention precision and safety. Stereotactic guiding and high-resolution real-time MRI imaging are combined in this research to improve medical navigation. The conceptual framework includes modeling the stereotactic system's magnetic field, real-time tracking of magnetic-sensored medical devices, and dynamic MRI imaging for continuous visibility throughout treatments. Stereotactic and MRI data can be fused for simultaneous vision and navigation, and adaptive path planning algorithms allow real-time targeting and avoidance of key structures. A simulated cardiac electrophysiology catheter ablation treatment shows the combined approach's potential benefits. Real-time adaptive navigation reduces radiation exposure and problems while targeting precisely. This research establishes a new medical navigation paradigm that improves precision, patient safety, and radiation exposure. This integrated method could revolutionize minimally invasive procedures across medical disciplines, despite limitations in patient-specific data integration and real-time algorithm development. This new navigation approach needs further research, validation, and clinical trials to confirm its feasibility and efficacy and improve medical patient care